Origin of Uterine Fibroids: Conversion of Myometrial Stem Cells to Tumor-Initiating Cells - Elkafas, Hoda; Qiwei, Yang; Al-Hendy, Ayman (Seminars in Reproductive Medicine, 2017)
Uterine fibroids (UFs) are the most frequent gynecologic tumors, affecting 70 to 80% of women over their lifetime, Although these tumors are benign, they can cause significant morbidity and may require invasive treatments such as myomectomy and hysterectomy in premenopausal women at a cost of up to $34 billion per year. Many risk factors for these tumors have been identified, including environmental exposures to endocrine-disrupting chemicals such as genistein and diethylstilbestrol (and other environmental agents) resulting in hyper-responsiveness to hormone in the adult uterus and promotion of hormone-dependent UFs. Although the molecular mechanisms underlying the pathogenesis of UFs is largely unknown, a growing body of evidence implicates unfavorable early-life environmental exposure and multiple biological pathways express as potentially import contributors. In this article, we will review the role of genetic and epigenetics in the conversion of myometrial stem cells to tumor (fibroid) initiating cells, and their role in UF development.
Keywords: myometrial stem cells; tumor-initiating cells; endocrine-disrupting chemicals; epigenetic reprograming; biology of uterine fibroids